Integrated kinematical & dynamics analysis of 2 track-start techniques - Vilas-Boas, J. P.; Cruz, M. J.; Sousa, F.; Conceicao, F.; Carvalho, J. M. (coachesinfo.com, 2000)
The purpose of this research was to characterise and compare two variants of the track-start technique for ventral swimming races, using simultaneous and synchronised dynamic and kinematic data. Results indicated that the track-start variant with rear projection of the centre of gravity (TSR) is able to produce higher impulses and velocities, but also implies higher periods in the starting block and presumably higher hydrodynamic drag values during entry, that imposes identical total times for the first 6m of the race, when compared with the track-start technique with forward projection of the centre of gravity (TSF).